The Economic Consequences of Abolishing Subminimum Wage Rates in South Africa. - Thukuse, Bulelani (The Easta Journal Law and Human Rights, 2025)
The purpose of this study is to examine the legal and economic ramifications of wage policy reforms in South Africa, particularly in relation to the abolition of subminimum wage rates. Minimum wage is a crucial step toward reducing income inequality and promoting social justice, the implementation of such policies may inadvertently create economic challenges. The study explores how wage reforms have been applied in a post-apartheid legal framework, considering whether they have effectively balanced worker rights with economic sustainability. By analysing legislative measures, court rulings, and economic trends, this paper investigates whether wage policies have contributed to meaningful socioeconomic progress or if they have, in some instances, hindered employment opportunities and economic stability. The authors will assess the extent to which wage reforms align with constitutional principles of fairness, equality, and human dignity. This study will also evaluate whether the state has effectively mitigated unintended consequences, such as job losses and reduced competitiveness for small businesses. This research further aims to explore whether wage increases have translated into tangible improvements in workers' quality of life, access to essential services, and overall economic participation. The authors hope that the arguments presented in this paper would assist in understanding the intricate balance between economic growth and labor rights, offering insights into the evolving role of wage policy in post-apartheid South Africa.